Pentingnya Nilai Persatuan Perpektif Al-Quran Surah Al-Imran Ayat 103 dalam Mengatasi Pandemi Covid-19 - Mukhtar (Jurnal Studi Al-Qur'an, 2021)
The values ​​and spirit of unity and the prohibition of division have long existed and are taught by Islam, as in Surah Al Imran verse 103. Based on the interpretation of Ibn Kasir, Al Misbah, and Al Qurtubi, it explains the importance of unity so that there is a "terrible" threat if it is violated. (enmity/ divorce). This indicates the importance of unity in life. Our scholars and founding fathers have also reminded us of the importance of unity. Departing from the importance of the value and spirit of unity, in the context of handling the spread of Covid-19, especially in Indonesia, the values ​​and spirit of unity need to be instilled in every heart because the values ​​and spirit of unity have long been taught and there are many examples of success due to the value of unity. This study focuses more on the study of interpretations (Ibn Kasir, Al Misbah, and Al Qurtubi) regarding surah Al Imran verse 103 and is associated with arguments and text texts that are relevant to the values ​​of unity. Through the descriptive method, Surah Al Imran verse 103 emphasizes that the existing values ​​of unity can be implemented in dealing with the Covid-19 pandemic, including framing unity in faith, unifying in the level of obedience, and uniting in warding off hoax & self-control.